Nights of rain and stars - Binchy, Maeve (New York Dutton, 2004)
In a small Greek island village, a group of travelers from around the world and the local residents they encounter are brought together when tragedy strikes.
Keywords: Irish -- Greece -- Fiction; Life change events -- Fiction; Taverns (Inns) -- Greece -- Fiction; Expatriation -- Fiction; Travelers -- Fiction; Greece -- Fiction